2003
DOI: 10.1677/erc.0.0100409
|View full text |Cite
|
Sign up to set email alerts
|

Validation of real-time RT-PCR for analysis of human breast cancer cell lines resistant or sensitive to treatment with antiestrogens.

Abstract: Using a quantitative real-time RT-PCR technique we have compared the expression of a number of genes in two different human breast cancer model systems for development of acquired resistance to antiestrogens. The model system developed at the Danish Cancer Society comprises the cell lines MCF-7, MCF-7/TAM R -1, MCF-7/182 R -6 and MCF-7/182 R -7, and the model system developed at the Lombardi Cancer Research Center consists of the cell lines MCF-7/LCC1, MCF-7/LCC2 and MCF-7/ LCC9. The findings on the well-known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 38 publications
7
39
0
1
Order By: Relevance
“…We determined the optimal concentration by analyzing its effect on the expression of a well-known estrogen responsive gene, the progesterone receptor (PR) (25). The concentration of 100 nM had the best efficiency, which is in accordance with a previous study (32). We observed that this concentration could inhibit E 2 -induced increase in the secretion of the two MMPs.…”
Section: Discussionsupporting
confidence: 91%
“…We determined the optimal concentration by analyzing its effect on the expression of a well-known estrogen responsive gene, the progesterone receptor (PR) (25). The concentration of 100 nM had the best efficiency, which is in accordance with a previous study (32). We observed that this concentration could inhibit E 2 -induced increase in the secretion of the two MMPs.…”
Section: Discussionsupporting
confidence: 91%
“…All ErbB receptors were expressed in the parental MCF-7 cells, but the level of EGFR mRNA was extremely low as also described in a previously published work [25]. Figure 1a shows mRNA levels of the four ErbB receptors in seven fulvestrant resistant sublines expressed relative to the level in parental MCF-7 cells.…”
Section: Expression Of the Erbb Receptors In Fulvestrant Resistant Brsupporting
confidence: 79%
“…Some examples of genes up-and down-regulated in MCF-7 MMU1 cells relative to wtMCF-7 cells following microarray analysis. ------------------------------------------------ ERα expression exceeded that of ERß in accord with other studies (32)(33)(34)(35)(36). This has also proven to be the case in a xenograft model of anti-estrogen resistance and in clinical breast cancer (37,38).…”
Section: Discussionsupporting
confidence: 91%
“…AIB-1 expression correlated with poorer prognosis in breast cancer and reduced response to hormonal therapy (15). Elevated levels of AIB-1 have been reported in other breast cancer cell studies (32,33,44,45). Elevated levels in our in vitro TAMr model strengthen the involvement of AIB-1 in breast carcinogenesis and its further elevation in TAMr suggests it may be contributory to this phenomenon.…”
Section: Discussionsupporting
confidence: 77%